On Statistical Convergence of Order α in Neutrosophic Normed Spaces - Shyamal Debnath; Bijoy Das; Santonu Debnath; Chiranjib Choudhury (Neutrosophic Sets and Systems, 2023)
In this paper, we introduce the notion of statistical convergent of order α in the neutrosophic normed spaces. We investigate a few properties of the newly introduced notion and examine the relationship with statistical convergence in the neutrosophic normed spaces. Finally, we introduce the concept of statistical Cauchy sequence of order α and show that statistical Cauchy sequences of order α are equivalent to statistical convergent of order α sequences in the neutrosophic normed spaces.